Reward Management System on Employee Motivation in MSMEs: A Systematic Literature Review - Esvanti, Mirza; Sopiah; Wardana, Ludi Wishnu (PT Maju Malaqbi Makkarana, 2025)
The role of MSMEs as a business enterprise service must certainly have a strategy to improve employee performance, one of which is appreciation for their performance and achievements in increasing revenue or profit for the organization. This research is a systematic literature study (SLR) that aims to analyze trends in scientific publications related to the development of Micro, Small and Medium Enterprises (MSMEs) from various aspects, including the type of document, scientific field, and country of origin of the author. The analysis shows that the majority of documents are scientific articles (83.3%), with the dominant fields including Business, Management and Accounting and Social Sciences (25% each). The largest source of publications came from the United Kingdom and Malaysia. This finding shows that there is considerable scientific attention to MSME development, especially from countries with strong entrepreneurial systems. In the Indonesian context, the results of this study provide an important illustration of the need for cross-disciplinary knowledge integration and the adoption of research-based policies from other countries to strengthen the competitiveness of national MSMEs. The study also recommends increased international collaboration and research focus on aspects of digitalization, innovation and sustainability in the development of MSMEs in Indonesia.